Diversity and Inclusion Initiatives: Influence on Organizational Performance - Purwoko, Bambang (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Employee retention is an important challenge for organizations today. This study proposes a research framework for understanding how diversity and inclusion can influence employee retention through job satisfaction. The theoretical basis of this research is based on existing literature on inclusive leadership, quality of work life, work-life balance, leaders' emotional intelligence, and compensation as factors that influence job satisfaction. The proposed model proposes that diversity and inclusion have a positive indirect effect on employee retention through job satisfaction. Further research using this framework can help organizations develop strategies to increase employee retention by building more diverse and inclusive work environments.